The cost of doubt: assessing the association between attributional ambiguity and mental health. - Cuevas, Adolfo G; Williams, David R; Krobath, Danielle M; Lyngdoh, Adiammi.; Kaba-Diakité, Fatoumata.; Allen, Jennifer D (Tufts University. Tisch Library., 2024)
Keywords: Attributional ambiguity, Discrimination, Mental health.; Springer Open.